RETRACTED: Assessment of Microplastics in Water and Sediment of River Benue Troughs, Benue State, Nigeria - Adam, Idris Habiba; Mohammed, Ikrimah Usman; Umaru, Isaac John (African Journal of Biochemistry and Molecular Biology Research, 2024)
Microplastics (MPs) are emerging environmental contaminants with significant ecological and health implications. This study investigates the presence and risks of microplastics (MPs) in the River Benue, Nigeria, using Fourier Transform Infrared (FTIR) spectroscopy. Water and sediment samples were collected from five locations along the river, with FTIR analysis revealing key functional groups such as alcohols, alkenes, amines, and carbonyls. Specifically, water samples from one site showed peaks at 3320 cm⁻¹ (O-H stretch, indicating alcohols) and 1640 cm⁻¹ (C=C stretch, indicating alkenes), while another site exhibited peaks at 3264 cm⁻¹ (N-H stretch, indicating amines) and 1640 cm⁻¹ (C=C stretch, indicating alkenes). Sediment samples showed significant peaks at 3622 cm⁻¹ (O-H stretch, indicating alcohols and phenols) and 2326 cm⁻¹ (C=N stretch, indicating nitriles). The Pollution Load Index (PLI) and Risk Quotient (RQ) analyses confirmed varying levels of microplastic contamination, with potential environmental and health risks due to the leaching of toxic additives. The study underscores the need for continuous monitoring, stricter pollution control, and public education to mitigate microplastic pollution in this vital waterway.